Investigative interviewing : adopting a forensic mindset - Grimes, John E., III (Milton Park, Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2021)
"Investigative Interviewing: Adopting a Forensic Mindset aims to promote legal and ethical investigative interview methods. Accordingly, possessing a forensic mindset should be the foundation that governs every aspect of an investigative interviewer's actions. Being a forensic professional-which includes the field of forensic interviewing-infers that one applies the highest standards in collecting, analyzing, preserving, and presenting evidence to a court of law or other tribunals. The term "investigative interview" with an interviewer's forensic mindset can be used to achieve all interview objectives, even obtaining truthful confessions that stand up to the scrutiny of the courts and public opinion. Key to this, the author contends, is eliminating the term "interrogation" and the confession-obtaining mindset it creates. In its place, the term "investigative interview" is used, promoting a forensic mindset to achieve desired interview objectives. What transpires during the interview must stand up to the scrutiny of the courts and public opinion. In this regard, due process, documenting the procedure, and practicing proven, effective techniques is paramount to getting to the truth-the ultimate goal of any investigation. The book includes a chapter dedicated to false confessions, due to is criticality and frequent occurrences of this. It continues with a discussion on the desired qualities of an investigative interviewer and strategies to break down barriers and gain trust with reluctant, uncooperative, and hostile interviewees. Proper report writing, an underrated key to any interview and investigation, is addressed in detail. Lastly. the book provides training on best practice interview steps and strategies to lead the interviewee to the truth that will stand up to the scrutiny of the courts and public opinion. Investigative Interviewing: Adopting a Forensic Mindset is well-suited as a textbook-outlining techniques and detailing all relevant case law concerning confessions- in addition to providing an Instructor's Manual with Test Bank and PowerPoint slides for professors to utilize in classroom instruction"--
Keywords: Interviewing in law enforcement; Forensic sciences; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement; PSYCHOLOGY / Assessment, Testing & Measurement